Risk Factors for Contact Lens–Related Microbial Keratitis: A Case–Control Multicenter Study. Issue 3 (May 2016) - Sauer, Arnaud; Meyer, Nicolas; Bourcier, Tristan
Abstract : Purpose: The most feared complication of contact lens (CL) wear is microbial keratitis (MK), even though its incidence remains low. This study aimed to identify the risk factors of CL-related MK in a large, prospective, multicenter case–control study. Methods: A multicenter case–control study was designed. The CL-related MK subpopulation (Case) was compared with healthy CL wearers (Control) using a 52-item anonymous questionnaire designed to determine subject demographics and lens wear history. Univariate and multivariate logistic regression analyses were performed to compare both groups. Results: The study enrolled 499 cases and 508 controls. The risk factors associated with the greatest increased odds of CL-related MK were as follows: using disinfecting solution more than 3 months (odds ratio [OR]=1.94), cosmetic CL wear and use of multipurpose disinfection solution (1.37 each), overnight wear, and soft lens use (OR=1.24 each). The protective factors associated with the greatest reduction in OR were fitting by an ophthalmologist (OR=0.73) and hyperopia versus myopia (OR=0.75). Conclusions: The infectious determinants were linked to the type of lenses, hygiene routine, CL handling, disinfecting solution, and storage case. This study aimed to highlight the increasingly CL-related MK, which likely occurs because of lack of patient information regarding basic rules of hygiene and CL care and handling.